Case Based Reasoning dan Similarity untuk Memprediksi Kondisi Keuangan Perusahaan - Halim Budi Santoso (Maranatha University Press, 2016)
Financial report is on of the tools to help managing the companies. Financial report can give clear picture about how good executives manage the company. Financial ratio is the measurement to know how the company daily operation and help to analyze situation within the organizations.Case based reasoning is one of problem solving methods which use past data to help solve current or future problems. Nearest Neighbor is one of the method in Case based reasoning to test similarity within past data and tested data. In this research, Case based reasoning is tested and implemented to predict future financial reports. This research use sample data from public company which is listed in Indonesia Stock Exchange. Some financial ratios are used to help future company financial condition.This study found that Case based reasoning is one of the method to predict company financial ratio. With Case based reasoning, it gives a clear description to find appropriate and suitable case as a reference. Keywords— Case based reasoning, Financial Forecasting, Financial Time Series, Bursa Efek Indonesia